Hybrid electrospun chitosan-phospholipids nanofibers for transdermal drug delivery - Mendes, Ana Carina Loureiro; Halter, Natalia; Schneider, Stefan W. (International journal of pharmaceutics, 2016)
Chitosan (Ch) polysaccharide was mixed with phospholipids (P) to generate electrospun hybrid nanofibers intended to be used as platforms for transdermal drug delivery. Ch/P nanofibers exibithed average diameters ranging from 248±94nm to 600±201nm, depending on the amount of phospholipids used. Fourier Transformed Infra-Red (FTIR) spectroscopy and Dynamic Light Scattering (DLS) data suggested the occurrence of electrostatic interactions between amine groups of chitosan with the phospholipid counterparts. The nanofibers were shown to be stable for at least 7days in Phosphate Buffer Saline (PBS) solution. Cytotoxicity studies (WST-1 and LDH assays) demonstrated that the hybrid nanofibers have suitable biocompatibility. Fluorescence microscopy, also suggested that L929 cells seeded on top of the CH/P hybrid have similar metabolic activity comparatively to the cells seeded on tissue culture plate (control). The release of curcumin, diclofenac and vitamin B12, as model drugs, from Ch/P hybrid nanofibers was investigated, demonstrating their potential utilization as a transdermal drug delivery system.